Diagnosis of aortic interruption by CT angiography - Shirani, Shapour (International Scientific Literature, Inc., 2013)
BACKGROUND: Interrupted aortic arch (IAA) is a rare congenital malformation of the aortic arch, which might be accompanied with other coexisting cardiovascular anomalies. CASE REPORT: Many cases with IAA are diagnosed at their neonatal and newborn period but in rare cases the diagnosis is not established until adulthood. The patients may have no clinical symptoms but the signs of heart failure will gradually appear and may cause death. RESULTS: The development of imaging methods such as computed tomography (CT) and magnetic resonance (MR) imaging has dramatically changed the diagnostics. Here we report a 20-year-old young man with IAA associated with sinus venosus atrial septal defect (SVD) and partial anomalous pulmonary venous connection (PAPVC) referred to our hospital.